Only truth : a novel of suspense - Cameron, Julie (Suspense fiction writer) (Scarlet, 2020)
"A successful artist with a doting husband, Isabel Dryland knows she should be grateful for her happy life. It's a complete reversal from the one she led before, when normalcy seemed out of reach, after a violent assault she cannot remember left her shattered and scarred. Even though the memory was lost, the nagging feeling that she was damaged goods and the lingering effects of her injuries kept her questioning her sanity at times. Tom, her husband, thinks a move will be the fresh start they need, and has even found the perfect house: a country estate that reminds him of one he admired in his youth. But all Isabel feels when she visits is an overwhelming sense of dread. Betrayed by her instincts so often before, she decides to trust Tom's, to accept the move and learn to love their new home over time. Instead, she learns that beneath the pretty facade of their new home lurk dark secrets powerful enough to bring her own trauma back to the fore. There is an uncanny familiarity about the place, as if it were infected by the experiences she hoped to escape. And the recurring presence of a mysterious stranger further disturbs her, giving her the sensation of being a predator's stalked prey. Isabel struggles to determine whether her fear is caused by memory alone, or by threats existing very much in the present. To find out, she'll have to finally close the book on what occurred so many years ago--but how do you heal from a past you cannot recall, when only the truth about your past can set you free?"--Provided by publisher